Impact of High-Efficacy Therapies for Multiple Sclerosis on B Cells - Federica Galota; Simone Marcheselli; Sara De Biasi; Lara Gibellini; Francesca Vitetta; Alessia Fiore; Krzysztof Smolik; Giulia De Napoli; Martina Cardi; Andrea Cossarizza; Diana Ferraro (Cells)
Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative autoimmune disorder of the central nervous system characterized by demyelination and neurodegeneration. Traditionally considered a T-cell-mediated disease, the crucial role of B lymphocytes in its pathogenesis, through different mechanisms contributing to inflammation and autoreactivity, is increasingly recognized. The risk of long-term disability in MS patients can be reduced by an early treatment initiation, in particular with high-efficacy therapies. The aim of this review is to provide an overview of the mechanisms of action of high-efficacy therapies for MS, with a focus on their impact on B cells and how this contributes to the drugs’ efficacy and safety profiles. Anti-CD20 monoclonal antibodies, Alemtuzumab, Cladribine and sequestering therapies encompassing Natalizumab and S1P receptors modulators will be discussed and emerging therapies, including Bruton’s Tyrosine Kinase inhibitors, will be presented.